Invoking Magna Carta: Locating Information Objects and Meaning in the 13th to 19th Centuries. (19th June 2015) - Lock, Alexander; Sims, Jonathan
Abstract: This article by Alexander Lock and Jonathan Sims describes the context in which Magna Carta was obtained. It distinguishes different versions of the charter and signposts particular documents and publications in the history of its transmission and interpretation up to the early nineteenth century. It also identifies various texts and objects which have indicated the charter's significance for groups and individuals at particular junctures. These include information carrying objects which might support research on Magna Carta within the context of the circulation and reception of legal meaning. A major focus of the article is a chronological account of the charter's invocation from the thirteenth century to the early nineteenth century.